Russian politics and geographical variable fixed in under the geostrategic changes (A study in the geo-political perspective and geopolitics) - مهيمن عبد الحليم الوادي (College of Education for Women, 2019)
The purpose of this study is to show the constants and variables geography in Russian policy in light of variables geostrategic witnessed by the world, especially after the collapse of the Soviet Union and the disintegration to fifteen Republic became the Russian Federation and the heir to the Soviet Union, Geography particularly important because the impact of its data in policy making less change ofothers, and explain the political choices cannot achieve security through its relationship constants geographical (natural or human) paint forms of economic activity and determine the points they national security. issue is the geographical this or that country is determined by its policy also specifies the way in which thinks policy makers by the short-termand long term. here comes the importance of the study to analyze and detect the strengths and weakness in the Russian Federation and its impact on policymaking and what is the role that can be played on the stage of international politics and in particular the Arab world.